Bacterial Leaching of Refractory Gold Ores - Bernhard J. Ralph (The Minerals, Metals and Materials Society, 1989)
In refractory gold ores much of the gold occurs in sub-microscopic form in sulfide minerals, most commonly pyrite and arsenopyrite Bacterial leaching is being developed as a pretreatment for these minerals to aid the liberation of gold and a variety of extracting reagents. This paper reviews the nature of the principal micro-organisms involved, the effects of various physico-chemical factors on the rate and extent of extraction, and likely mechanisms involved.